Continuous preparation method of para-aramid polymer

By performing prepolymerization in a single channel micro reactor, the problems of poor mixing uniformity of materials and uneven reaction heat in the preparation of polyterephthalyl paraphenylenediamine fibers were solved, and high-quality preparation of para-aramid polymers was achieved, and high-performance fibers with narrow molecular weight distribution and stable performance were obtained.

CN119798648AActive Publication Date: 2025-04-11JIANGSU SHENGBANG NEW MATERIALS CO LTD

Patent Information

Application Number
CN202510001317.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-02
Publication Date
2025-04-11
Estimated Expiration
2045-01-02

AI Technical Summary

Technical Problem

In the prior art, when preparing high-performance polyterephthalyl terephthalyl terephthalidine fibers, it is difficult to obtain high-performance aramid fibers, such as poor mixing uniformity of materials, uneven reaction heat, widening molecular weight distribution, low weight average molecular weight, and many by-products.

Method used

A two-step polymerization method is adopted, in which the prepolymerized part is carried out in a single channel micro reactor. Using the micro-size of the micro-channel and the design surrounding the feed channel, the sufficient contact and heat exchange between the material and the runner wall are achieved, and the reaction heat is quickly removed to ensure uniform temperature.

Benefits of technology

The para-aramid polymer obtained by this method has the characteristics of narrow molecular weight distribution, stable performance and good particle size uniformity, which avoids the problem of local temperature difference in traditional reactors and ensures the high quality and high performance of the polymer.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119798648A_ABST
    Figure CN119798648A_ABST
Patent Text Reader

Abstract

The invention provides a continuous preparation method of a para-aramid polymer. The continuous preparation method comprises the following steps: (a) mixing p-phenylenediamine and a polar solvent to obtain a p-phenylenediamine solution; (b) melting the terephthaloyl chloride to obtain molten terephthaloyl chloride; (c) introducing the p-phenylenediamine solution prepared in the step (a) and part of the molten-state terephthaloyl chloride prepared in the step (b) into a micro-channel reactor for reaction to obtain a prepolymer; (d) mixing the prepolymer prepared in the step (c) with the remaining molten terephthaloyl chloride prepared in the step (b), and reacting to obtain a para-aramid polymer; and the micro-channel reactor is a single-channel micro-reactor. According to the continuous preparation method provided by the invention, the materials are uniformly mixed, the reaction heat can be quickly removed, the side reaction is effectively controlled, and the prepared para-aramid polymer has the characteristics of narrow molecular weight distribution, stable performance and good particle size uniformity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of aramid preparation, and in particular relates to a continuous preparation method of a para-aramid polymer. Background Art

[0002] Poly(p-phenylene terephthalamide) (PPTA) fiber was synthesized by DuPont in the United States in 1965 using a low-temperature solution polycondensation reaction. The dry-jet wet spinning method was invented using the liquid crystal behavior of PPTA / H2SO4 solution to obtain high-performance poly(p-phenylene terephthalamide) fiber, which is called para-aramid or aramid 1414 in my country. It is a high-performance aromatic polyamide fiber. The fiber has excellent properties such as high strength, high modulus, high temperature resistance, acid resistance, alkali resistance and low density. Its specific tensile strength is 8 times that of steel wire (≥5Gpa), and its specific modulus is 3 to 4 times that of steel wire (≥148Gpa). Therefore, it has important applications in aerospace, national defense, automotive industry and sports equipment.

[0003] The industrial production of aramid 1414 fiber adopts a two-step process, that is, polymerization first and then spinning. The currently industrialized method for preparing poly(p-phenylene terephthalamide) is the low-temperature solution polycondensation method. The specific preparation process is: dissolve calcium chloride (CaCl2) in N-methylpyrrolidone to prepare CaCl2-NMP solvent, dissolve p-phenylenediamine (PPDA) in the CaCl2-NMP solvent, and then add terephthaloyl chloride (TPC) in an equal molar ratio. The low-temperature solution polycondensation method is used to obtain poly(p-phenylene terephthalamide) polymer under high-speed shearing. Continuous polymerization or intermittent polymerization can be used. The polymerization reaction is shown in the following formula:

[0004]

[0005] During the low-temperature polycondensation process, the viscosity of the mixture increases rapidly with the increase of molecular weight, and the mixture gradually changes phase from liquid to solid, making it very difficult to mix the reactants; due to the high activity of the reactive monomers of poly(p-phenylene terephthalamide), the process requires strict isolation of oxygen and water, and because the polycondensation reaction is very rapid and highly exothermic (reaction enthalpy is -107 kJ / mol), when using a traditional reactor, an efficient heat exchange system is required to ensure that the temperature of the mixture is sufficiently low and uniform, so as to obtain a polymer with a high weight-average molecular weight and a narrow molecular weight distribution. However, the temperature in the reactor is prone to unevenness, and the local temperature is high, resulting in problems such as a widening of the molecular weight distribution, a low weight-average molecular weight, and many by-products, making it difficult to obtain high-performance aramid fibers. At the same time, polymerization reactions are a hazardous chemical process that is under national key supervision, and are also a major problem that needs to be solved in the development of the industry.

[0006] Therefore, it is necessary to develop a continuous preparation method for para-aramid polymers that can mix materials evenly and solve the problem of uneven heat exchange and uneven temperature in the reactor. Summary of the invention

[0007] In view of the deficiencies in the prior art, the object of the present invention is to provide a continuous preparation method for a para-aramid polymer, in which materials are mixed evenly, reaction heat can be quickly removed, and the occurrence of side reactions is effectively controlled. The prepared para-aramid polymer has the characteristics of narrow molecular weight distribution, stable performance, and good particle size uniformity.

[0008] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:

[0009] The present invention provides a continuous preparation method of a para-aramid polymer, the continuous preparation method comprising the following steps:

[0010] (a) mixing p-phenylenediamine and a polar solvent to obtain a p-phenylenediamine solution, wherein the mass concentration of water in the p-phenylenediamine solution is ≤200 ppm, such as 40 ppm, 60 ppm, 80 ppm, 100 ppm, 120 ppm, 140 ppm, 160 ppm or 180 ppm.

[0011] (b) melting terephthaloyl chloride to obtain molten terephthaloyl chloride;

[0012] (c) introducing the p-phenylenediamine solution obtained in step (a) and part of the molten terephthaloyl chloride obtained in step (b) into a microchannel reactor for reaction to obtain a prepolymer;

[0013] (d) mixing the prepolymer obtained in step (c) with the remaining molten terephthaloyl chloride obtained in step (b), and reacting them to obtain a para-aramid polymer;

[0014] The steps (a) and (b) are performed in no particular order, or simultaneously;

[0015] The microchannel reactor is a single channel microreactor, comprising a first body 101, a second body 102, a microchannel feed port 201, a microchannel 202, a microchannel outlet 203, a feed channel feed port 301, a feed channel 302, and a feed channel outlet 303, wherein the feed channel 302 is an annular cavity surrounding the microchannel 202;

[0016] The feed channel outlet 303 is connected to the microchannel 202 and is arranged at a position close to the microchannel feed port 201. In the step (c), the molten terephthaloyl chloride flows into the microchannel reactor from the microchannel feed port 201; the p-phenylenediamine solution flows into the microchannel reactor from the feed channel feed port 301, and the prepolymer flows out of the microchannel reactor from the microchannel outlet 203. The flow direction of the p-phenylenediamine solution in the feed channel 302 is opposite to the flow direction of the fluid in the microchannel 202.

[0017] In the present invention, a two-step polymerization is adopted, wherein the prepolymerization part adopts a single channel microreactor for polymerization, and the microchannel diameter of the single channel microreactor is small, so that the material in the microchannel can fully contact the flow channel wall of the microchannel for heat dissipation, and the p-phenylenediamine solution with a lower temperature surrounds the microchannel, which can quickly take away the heat generated by the reaction in the microchannel, making the heat distribution more uniform and reaching a balance, avoiding the heat generated by the reaction from accumulating in the microchannel to cause the reaction to run away, and effectively controlling the safety risk of the polymerization reaction. Compared with the traditional reactor, the microchannel reactor of the present invention removes the reaction heat more quickly, the material temperature is uniform, and there is no problem of large local temperature difference. Therefore, the molecular weight of the obtained prepolymer is consistent, and the molecular weight distribution is narrower. A good prepolymer can ensure that the growth rate of the polymer molecular weight is consistent during the final polymerization, and the final polymer molecular weight distribution is narrow, and there is no gel phenomenon; it also avoids the problem of complex structure and many dead zones of using multi-stage parallel microreactors. The continuous preparation method of the para-aramid polymer continuous polymerization method is a micro-unit polymerization reaction, and the amount of online reactants is small, which is safer and controllable.

[0018] Preferably, a guide groove is provided at the discharge port 303 of the feed channel.

[0019] In the present invention, a guide groove is provided at the discharge port 303 of the feed channel, so that the p-phenylenediamine solution can enter the microchannel through the guide groove and form a vortex, which further increases the heat exchange between the mixed material in the microchannel and the flow channel wall of the microchannel, and avoids the temperature unevenness of the traditional reactor due to uneven heat exchange, such as high internal material temperature and low external material temperature, thereby obtaining a p-aramid polymer with high molecular weight and narrow molecular weight distribution.

[0020] Preferably, the diameter of the microchannel 202 is ≤3 mm, for example, 0.5 mm, 1 mm, 1.5 mm, 2 mm or 2.5 mm.

[0021] Preferably, the microchannel reactor is made of any one of glass, metal or polymer material, more preferably metal.

[0022] Preferably, the polar solvent in step (a) comprises N-methylpyrrolidone.

[0023] Preferably, the mixing in step (1) further includes mixing with a co-solvent.

[0024] Preferably, the co-solvent comprises calcium chloride or lithium chloride.

[0025] Preferably, the cosolvent is calcium chloride, and the mass percentage of calcium chloride in the p-phenylenediamine solution is 7% to 10%, for example, 7.3%, 7.6%, 7.9%, 8.2%, 8.5%, 8.8%, 9.1%, 9.4% or 9.7%.

[0026] Preferably, the cosolvent is lithium chloride, and the mass percentage of lithium chloride in the p-phenylenediamine solution is 2% to 3%, for example, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8% or 2.9%, etc.

[0027] Preferably, the mass percentage of p-phenylenediamine in the p-phenylenediamine solution of step (a) is 3% to 8%, for example, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7% or 7.5%, etc.

[0028] Preferably, the temperature of the p-phenylenediamine solution in step (a) is 0 to 15°C (eg, 2°C, 4°C, 6°C, 8°C, 10°C, 12°C or 14°C, etc.), more preferably 4 to 6°C.

[0029] Preferably, the temperature of the molten terephthaloyl chloride in step (b) is 85-95° C. (e.g., 86° C., 87° C., 88° C., 89° C., 90° C., 91° C., 92° C., 93° C. or 94° C., etc.).

[0030] Preferably, the spraying direction of the p-phenylenediamine solution at the outlet 303 of the feed channel in the microchannel reactor is at an angle of 15° to 75° to the microchannel 202 .

[0031] In the present invention, by making the spray direction of the p-phenylenediamine solution form an angle of 15° to 75° with the microchannel, the p-phenylenediamine solution can enter the microchannel and form a mixed material with molten terephthaloyl chloride to flow along the microchannel toward the outlet, that is, the p-phenylenediamine solution and the molten terephthaloyl chloride can be evenly mixed and fully contacted, the reaction rate is improved, and the heat exchange between the mixed material and the flow channel wall of the microchannel is increased, thereby avoiding the temperature unevenness phenomenon of high internal material temperature and low external material temperature caused by uneven heat exchange in a traditional reactor, thereby obtaining a p-aramid polymer with high molecular weight and narrow molecular weight distribution.

[0032] Preferably, in step (c), the injection speed of the p-phenylenediamine solution into the microchannel 202 is 0.3-2 m / s.

[0033] (For example, 0.5m / s, 0.7m / s, 0.9m / s, 1.1m / s, 1.3m / s, 1.5m / s, 1.7m / s or 1.9m / s, etc.), more preferably 1.2m / s, the flow rate is 0.45-3 tons / hour, for example, 0.5 tons / hour, 1 ton / hour, 1.5 tons / hour, 2 tons / hour or 2.5 tons / hour, etc.

[0034] Preferably, in step (c), the flow rate of the molten terephthaloyl chloride entering the microchannel 202 is 0.8-1.6 m / s (e.g., 0.9 m / s, 1.0 m / s, 1.1 m / s, 1.2 m / s, 1.3 m / s, 1.4 m / s or 1.5 m / s, etc.).

[0035] Preferably, the length of the microchannel 202 is 20-50 cm, for example, 23 cm, 26 cm, 29 cm, 32 cm, 35 cm, 38 cm, 41 cm, 44 cm or 47 cm.

[0036] Preferably, the ratio of the molar amount of the molten terephthaloyl chloride in step (c) to the molar amount of p-phenylenediamine in the p-phenylenediamine solution in step (c) is (0.3-0.7):1, for example, 0.35:1, 0.4:1, 0.45:1, 0.5:1, 0.55:1, 0.6:1 or 0.65:1, etc.

[0037] Preferably, the reaction temperature in step (c) is 0-25°C, for example, 3°C, 6°C, 9°C, 12°C, 15°C, 18°C, 21°C or 24°C.

[0038] The heat generated by the reaction in step (c) of the continuous preparation method of the present invention is absorbed by the p-phenylenediamine solution, so that the heat distribution is more uniform, the heat accumulation generated by the reaction in the microchannel is reduced, and the temperature stability can be achieved during the continuous preparation process. After the reaction, the heat and products are discharged from the discharge port of the microchannel.

[0039] Preferably, the ratio of the total molar amount of the molten terephthaloyl chloride in step (c) and step (d) to the molar amount of p-phenylenediamine in the p-phenylenediamine solution in step (c) is 0.99 to 1.01:1, for example, 0.992:1, 0.994:1, 0.996:1, 0.998:1, 1.000:1, 1.002:1, 1.004:1, 1.006:1 or 1.008:1, etc.

[0040] Preferably, the reaction in step (d) is carried out in a twin-screw reactor or a tank reactor.

[0041] Preferably, the aspect ratio of the twin-screw reactor is ≤10, such as 5, 6, 7, 8 or 9.

[0042] Preferably, the gap between the inner wall of the barrel of the twin-screw reactor and the screw element is ≤2 mm, for example, 0.2 mm, 0.4 mm, 0.6 mm, 0.8 mm, 1.0 mm, 1.2 mm, 1.4 mm, 1.6 mm or 1.8 mm.

[0043] The screw element in the present invention includes a thread element and / or a meshing element.

[0044] Preferably, the stirring rate of the autoclave reactor is ≥300 rpm (e.g., 350 rpm, 400 rpm, 450 rpm, 500 rpm, 550 rpm, 600 rpm, 650 rpm or 700 rpm, etc.), more preferably ≥500 rpm.

[0045] Preferably, the gap between the maximum outer diameter of the agitator of the autoclave reactor and the cylinder wall is ≤2 mm, for example, 0.2 mm, 0.4 mm, 0.6 mm, 0.8 mm, 1.0 mm, 1.2 mm, 1.4 mm, 1.6 mm or 1.8 mm.

[0046] Preferably, the reaction temperature in step (d) is ≤40°C, for example 5°C, 10°C, 15°C, 20°C, 25°C, 30°C or 35°C, and the reaction time is 10 to 40 min, for example 13 min, 16 min, 19 min, 21 min, 23 min, 25 min, 28 min, 31 min, 34 min or 37 min, etc.

[0047] Preferably, the reaction in step (d) further comprises the steps of neutralization, washing and drying.

[0048] Compared with the prior art, the present invention has the following beneficial effects:

[0049] The continuous preparation method of the para-aramid polymer of the present invention is a micro-unit polymerization reaction, which adopts a two-step polymerization method, wherein the prepolymerization part adopts a microchannel reactor for polymerization, and the amount of online reactants is small, which can effectively control the release of reaction heat, is safer and controllable, and effectively controls the safety risk of the polymerization reaction. The microchannel reactor is a single-channel microreactor. Compared with the traditional reactor, the reaction heat is removed more quickly, the material temperature state is uniform, and there is no problem of large local temperature difference. Therefore, the molecular weight of the obtained prepolymer is consistent, and the molecular weight distribution is more uniform. A good prepolymer can ensure that the growth rate of the polymer molecular weight is consistent during the final polymerization, and the final polymer molecular weight distribution is narrow, and there is no gel phenomenon, and the particle size uniformity is good; it also avoids the problem of complex structure and many dead zones of using multi-stage parallel microreactors. The continuous preparation method of the para-aramid polymer of the present invention has high output, and can realize the production of para-aramid polymer with a single-line annual production capacity of thousands of tons. The para-aramid polymer prepared by the continuous preparation method of the para-aramid polymer is used for spinning, and the obtained aramid fiber has stable performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0050] Figure 1 is a cross-sectional view of a microchannel reactor;

[0051] Among them, 101-first body, 102-second body, 201-microchannel feed inlet, 202-microchannel, 203-microchannel outlet, 301-feeding channel feed inlet, 302-feeding channel, 303-feeding channel outlet;

[0052] Figure 2 Schematic diagram of the mixed material flowing along the microchannel in a swirling manner. DETAILED DESCRIPTION

[0053] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0054] Example 1

[0055] This embodiment provides a continuous preparation method of a para-aramid polymer, the continuous preparation method comprising the following steps:

[0056] (a) p-phenylenediamine, a polar solvent (N-methylpyrrolidone) and calcium chloride are mixed to obtain a p-phenylenediamine solution, wherein the mass percentage of calcium chloride in the p-phenylenediamine solution is 7%, the mass concentration of water is 150 ppm, the mass percentage of p-phenylenediamine is 5%, and the temperature of the p-phenylenediamine solution is 5°C.

[0057] (b) melting terephthaloyl chloride to obtain molten terephthaloyl chloride, wherein the temperature of the molten terephthaloyl chloride is 90°C.

[0058] (c) introducing the p-phenylenediamine solution obtained in step (a) and part of the molten terephthaloyl chloride obtained in step (b) into a microchannel reactor for reaction, wherein the molar ratio of p-phenylenediamine to terephthaloyl chloride is 1:0.3, to obtain a prepolymer;

[0059] The above-mentioned microchannel reactor is a single channel microreactor, and the material is 316 stainless steel. Figure 1 As shown, it includes a first body 101, a second body 102, a microchannel feed port 201, a microchannel 202, a microchannel outlet 203, a feed channel feed port 301, a feed channel 302, and a feed channel outlet 303, wherein the feed channel 302 is an annular cavity surrounding the microchannel 202;

[0060] The material delivery channel outlet 303 is connected to the microchannel 202 and is arranged near the microchannel feed port 201. A guide groove is arranged at the material delivery channel outlet 303 to form a swirl flow. Figure 2 As shown; in the step (c), the molten terephthaloyl chloride flows into the microchannel reactor from the microchannel feed port 201; the p-phenylenediamine solution flows into the microchannel reactor from the feed channel feed port 301, and the prepolymer flows out of the microchannel reactor from the microchannel discharge port 203, and the flow direction of the p-phenylenediamine solution in the feed channel 302 is opposite to the flow direction of the molten terephthaloyl chloride in the microchannel 202.

[0061] The diameters of the microchannel feed port 201, the microchannel 202 and the microchannel discharge port 203 are the same, which is 3 mm. The flow rate of the molten terephthaloyl chloride into the microchannel 202 is 1.2 m / s. The length of the microchannel 202 is 50 cm.

[0062] The injection direction of the p-phenylenediamine solution at the outlet 303 of the feed channel in the microchannel reactor is at an angle of 30° to the microchannel 202. The injection speed of the p-phenylenediamine solution entering the microchannel 202 is 0.8 m / s, and the flow rate is 2 tons / hour.

[0063] (d) conveying the prepolymer prepared in step (c) and the remaining molten terephthaloyl chloride prepared in step (b) to a twin-screw reactor for reaction, wherein the ratio of the total molar amount of the molten terephthaloyl chloride in step (c) and step (d) to the molar amount of p-phenylenediamine in the p-phenylenediamine solution in step (c) is 1:1, the reaction temperature is 40° C., the reaction time is 20 min, the aspect ratio of the twin-screw reactor is 10, and the gap between the inner wall of the barrel of the twin-screw reactor and the screw element is 2 mm; and then neutralizing, washing and drying to obtain a para-aramid polymer.

[0064] Example 2

[0065] This embodiment provides a continuous preparation method of a para-aramid polymer, which differs from Embodiment 1 only in that, in step (a), the temperature of the p-phenylenediamine solution is adjusted to 10° C., in step (c), the spray direction of the p-phenylenediamine solution at the outlet of the feed channel in the microchannel reactor is adjusted to be at an angle of 15° with the microchannel, the flow rate of the molten terephthaloyl chloride entering the microchannel is 0.8 m / s, the spray speed of the p-phenylenediamine solution entering the microchannel 202 is 0.4 m / s, the flow rate is 1 ton / hour, and the molar ratio of p-phenylenediamine to terephthaloyl chloride in step (c) is changed to 1:0.4; other conditions are the same as those in Embodiment 1.

[0066] Example 3

[0067] This embodiment provides a continuous preparation method of a para-aramid polymer, which differs from Embodiment 1 only in that the flow rate of the molten terephthaloyl chloride entering the microchannel in step (3) is adjusted to 1.6 m / s, and the molar ratio of paraphenylenediamine to terephthaloyl chloride in step (c) is 1:0.4. Other conditions are the same as in Embodiment 1.

[0068] Comparative Example 1

[0069] This comparative example provides a method for preparing a para-aramid polymer, and the preparation method specifically comprises the following steps:

[0070] (a) p-phenylenediamine, a polar solvent (N-methylpyrrolidone) and calcium chloride are mixed to obtain a p-phenylenediamine solution, wherein the mass percentage of calcium chloride in the p-phenylenediamine solution is 7%, the mass concentration of water is 150 ppm, the mass percentage of p-phenylenediamine is 5%, and the temperature of the p-phenylenediamine solution is 5°C.

[0071] (b) melting terephthaloyl chloride to obtain molten terephthaloyl chloride, wherein the temperature of the molten terephthaloyl chloride is 90°C.

[0072] (c) conveying the p-phenylenediamine solution obtained in step (a) and the molten terephthaloyl chloride obtained in step (b) to a twin-screw reactor for reaction, wherein the molar ratio of the molten terephthaloyl chloride to the molar amount of p-phenylenediamine in the p-phenylenediamine solution is 1:1, the reaction temperature is 40° C., the reaction time is 20 min, the aspect ratio of the twin-screw reactor is 10, and the gap between the inner wall of the barrel of the twin-screw reactor and the screw element is 1 mm, and then neutralizing, washing and drying to obtain a p-aramid polymer.

[0073] Comparative Example 2

[0074] This comparative example provides a method for preparing a para-aramid polymer, and the preparation method specifically comprises the following steps:

[0075] (a) p-phenylenediamine, a polar solvent (N-methylpyrrolidone) and calcium chloride are mixed to obtain a p-phenylenediamine solution, wherein the mass percentage of calcium chloride in the p-phenylenediamine solution is 7%, the mass concentration of water is 150 ppm, the mass percentage of p-phenylenediamine is 5%, and the temperature of the p-phenylenediamine solution is 5°C.

[0076] (b) melting terephthaloyl chloride to obtain molten terephthaloyl chloride, wherein the temperature of the molten terephthaloyl chloride is 90°C.

[0077] (c) transporting the p-phenylenediamine solution obtained in step (a) and the molten terephthaloyl chloride obtained in step (b) to a conventional 10L small-scale stirred reactor for reaction, wherein the ratio of the molar amount of the molten terephthaloyl chloride to the molar amount of p-phenylenediamine in the p-phenylenediamine solution is 1:1, the reaction temperature is 40° C., the reaction time is 20 min, the stirring rate is 500 rpm, the maximum outer diameter of the stirrer in the stirred reactor and the clearance between the cylinder wall is 2 mm, and then neutralizing, washing and drying to obtain a p-aramid polymer.

[0078] Comparative Example 3

[0079] (a) p-phenylenediamine, a polar solvent (N-methylpyrrolidone) and calcium chloride are mixed to obtain a p-phenylenediamine solution, wherein the mass percentage of calcium chloride in the p-phenylenediamine solution is 7%, the mass concentration of water is 150 ppm, the mass percentage of p-phenylenediamine is 5%, and the temperature of the p-phenylenediamine solution is 5°C.

[0080] (b) melting terephthaloyl chloride to obtain molten terephthaloyl chloride, wherein the temperature of the molten terephthaloyl chloride is 90°C.

[0081] (c) transporting the p-phenylenediamine solution obtained in step (a) and part of the molten terephthaloyl chloride obtained in step (b) to a conventional 10 L small-scale stirred reactor for reaction, wherein the molar ratio of p-phenylenediamine to terephthaloyl chloride is 1:0.3, to obtain a prepolymer;

[0082] (d) mixing the prepolymer prepared in step (c) with the remaining molten terephthaloyl chloride prepared in step (b), and reacting them in a twin-screw reactor, wherein the ratio of the total molar amount of the molten terephthaloyl chloride in step (c) and step (d) to the molar amount of p-phenylenediamine in the p-phenylenediamine solution in step (c) is 1:1, the reaction temperature is 40° C., the reaction time is 20 min, the aspect ratio of the twin-screw reactor is 10, and the gap between the inner wall of the barrel of the twin-screw reactor and the screw element is 2 mm; and then neutralizing, washing and drying to obtain a para-aramid polymer.

[0083] The following performance tests were performed on the para-aramid polymers prepared in Examples 1-3 and Comparative Examples 1-3.

[0084] Inherent viscosity: The inherent viscosity of the prepared para-aramid polymer was measured 5 times, and the maximum and minimum values ​​measured were taken as the endpoints of the inherent viscosity range.

[0085] Particle size: The particle size distribution of the para-aramid polymer was tested using a particle size analyzer. The test results are shown in Table 1 below.

[0086] Table 1

[0087]

[0088]

[0089] In Table 1, “ / ” means that the test was not conducted.

[0090] From the test results in Table 1, it can be seen that the para-aramid polymer prepared by the continuous preparation method of the para-aramid polymer provided in Examples 1-3 has a logarithmic viscosity of 5 to 8, a relatively small CV value, and good particle size uniformity.

[0091] Compared with Example 1, if a microchannel reactor is not used for the reaction (Comparative Example 1) and a twin-screw reactor is used for polymerization, the inherent logarithmic viscosity of the obtained para-aramid polymer fluctuates greatly, the CV value reaches 20%, and larger and smaller particles account for a higher proportion.

[0092] Compared with Example 1, if a microchannel reactor is not used for the reaction (Comparative Example 2), and a conventional kettle-type stirred reactor is used for polymerization, the logarithmic viscosity of the obtained para-aramid polymer fluctuates greatly, the CV value reaches 30%, and larger and smaller particles account for a higher proportion.

[0093] Compared with Example 1, if a conventional kettle-type stirred reactor (Comparative Example 3) is used to prepare the prepolymer, the obtained prepolymer is not uniform enough, the reaction is not complete, and there are particles. The logarithmic viscosity of the para-aramid polymer finally obtained fluctuates greatly, and the CV value reaches 20%, with a high proportion of larger and smaller particles.

[0094] In summary, the para-aramid polymer prepared by the continuous preparation method of the para-aramid polymer provided by the present invention has a relatively small CV value and good particle uniformity.

[0095] The applicant declares that the present invention illustrates the process method of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned process steps, that is, it does not mean that the present invention must rely on the above-mentioned process steps to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of the raw materials selected by the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A continuous preparation method of a para-aramid polymer, characterized in that: The continuous preparation method comprises the following steps: (a) mixing p-phenylenediamine and a polar solvent to obtain a p-phenylenediamine solution, wherein the mass concentration of water in the p-phenylenediamine solution is ≤200 ppm; (b) melting terephthaloyl chloride to obtain molten terephthaloyl chloride; (c) introducing the p-phenylenediamine solution obtained in step (a) and part of the molten terephthaloyl chloride obtained in step (b) into a microchannel reactor for reaction to obtain a prepolymer; (d) mixing the prepolymer obtained in step (c) with the remaining molten terephthaloyl chloride obtained in step (b), and reacting them to obtain a para-aramid polymer; The steps (a) and (b) are performed in no particular order, or simultaneously; The microchannel reactor is a single channel microreactor, comprising a first body (101), a second body (102), a microchannel feed inlet (201), a microchannel (202), a microchannel outlet (203), a feed channel feed inlet (301), a feed channel (302), and a feed channel outlet (303), wherein the feed channel (302) is an annular cavity surrounding the microchannel (202); The feed channel outlet (303) is connected to the microchannel (202) and is arranged at a position close to the microchannel feed port (201). In the step (c), the molten terephthaloyl chloride flows into the microchannel reactor from the microchannel feed port (201); the p-phenylenediamine solution flows into the microchannel reactor from the feed channel feed port (301), and the prepolymer flows out of the microchannel reactor from the microchannel outlet (203). The flow direction of the p-phenylenediamine solution in the feed channel (302) is opposite to the flow direction of the fluid in the microchannel (202).

2. The continuous preparation method according to claim 1, characterized in that: A guide groove is provided at the discharge port (303) of the feed channel; Preferably, the diameter of the microchannel (202) is ≤3 mm; Preferably, the microchannel reactor is made of any one of glass, metal or polymer material.

3. The continuous preparation method according to claim 1 or 2, characterized in that: The polar solvent in step (a) comprises N-methylpyrrolidone.

4. The continuous preparation method according to any one of claims 1 to 3, characterized in that: The mixing in step (1) further comprises mixing with a co-solvent; Preferably, the co-solvent comprises calcium chloride or lithium chloride.

5. The continuous preparation method according to claim 4, characterized in that: The cosolvent is calcium chloride, and the mass percentage of calcium chloride in the p-phenylenediamine solution is 7% to 10%; Preferably, the co-solvent is lithium chloride, and the mass percentage of lithium chloride in the p-phenylenediamine solution is 2% to 3%.

6. The continuous preparation method according to any one of claims 1 to 5, characterized in that: The mass percentage of p-phenylenediamine in the p-phenylenediamine solution of step (a) is 3% to 8%.

7. The continuous preparation method according to any one of claims 1 to 6, characterized in that: The temperature of the p-phenylenediamine solution in step (a) is 0 to 15° C.; Preferably, the temperature of the molten terephthaloyl chloride in step (b) is 85-95° C.; Preferably, the spray direction of the p-phenylenediamine solution at the outlet (303) of the feed channel in the microchannel reactor is at an angle of 15° to 75° to the microchannel (202); Preferably, in step (c), the injection speed of the p-phenylenediamine solution into the microchannel (202) is 0.3 to 2 m / s, and the flow rate is 0.45 to 3 tons / hour; Preferably, in step (c), the flow rate of the molten terephthaloyl chloride entering the microchannel (202) is 0.8 to 1.6 m / s; Preferably, the length of the microchannel (202) is 20 to 50 cm.

8. The continuous preparation method according to any one of claims 1 to 7, characterized in that: The ratio of the molar amount of the molten terephthaloyl chloride in step (c) to the molar amount of p-phenylenediamine in the p-phenylenediamine solution in step (c) is (0.3-0.7): 1; Preferably, the reaction temperature in step (c) is 0 to 25°C; Preferably, the ratio of the total molar amount of the molten terephthaloyl chloride in step (c) and step (d) to the molar amount of p-phenylenediamine in the p-phenylenediamine solution in step (c) is 0.99 to 1.01:

1.

9. The continuous preparation method according to any one of claims 1 to 8, characterized in that: The reaction in step (d) is carried out in a twin-screw reactor or a tank reactor; Preferably, the aspect ratio of the twin-screw reactor is ≤10; Preferably, the gap between the inner wall of the barrel of the twin-screw reactor and the screw element is ≤2 mm; Preferably, the stirring rate of the autoclave reactor is ≥300 rpm, more preferably ≥500 rpm; Preferably, the gap between the maximum outer diameter of the agitator of the kettle reactor and the cylinder wall is ≤2 mm.

10. The continuous preparation method according to any one of claims 1 to 9, characterized in that: The reaction temperature in step (d) is ≤40°C and the reaction time is 10 to 40 minutes; Preferably, the reaction in step (d) further comprises the steps of neutralization, washing and drying.

Citation Information

Patent Citations

  • Micro-reaction system and micro-reaction method for preparing para / meta-aramid

    CN104667846A

  • A method for preparing aromatic polyamide fiber by adopting a micro-reactor

    CN107200843A

  • Ultrasonic atomization micro-mixer, micro-channel reactor, prepolymerization system and para-aramid resin continuous polymerization reaction system and method

    CN110605079A

  • Method and system for continuously preparing para-aramid polymer

    CN116023653A

  • Method for preparing aramid fiber polymer with narrow particle size distribution in continuous polymerization-solution feeding mode

    CN118459752A

Cited By

  • Solution sample introduction polymerization method of heterocyclic aramid

    CN121495114A